This Barbie Can Walk on Water! Longing for a Feminist Messiah in the Cinema - van Es, M.A. (Routledge, 2025)
This chapter explores the creative potential of Hollywood blockbusters in relation to gender and sexuality by discussing whether Stereotypical Barbie in Greta Gerwig’s fantasy film Barbie could be seen as a feminist messiah-figure. The author argues that the film subtly appropriates and reimagines religious themes in order to centre the experiences and perspectives of women instead of men, instil a desire for a better world and encourage feminist solidarity. Yet, the chapter also suggests that, ultimately, the film confronts us with the impossibility of a feminist messiah-figure, given the complexity of contemporary feminism. Thus, in the final part of this chapter, the author critically reflects on her own emotional responses to Barbie – from high expectations to intense enjoyment to an odd sense of disappointment – as well as on other feminist critiques of the film, presenting some thoughts about what it means to long for a feminist messiah in the cinema.
Keywords: Taverne; SDG 5 - Gender Equality